Technological Pedagogical Content Knowledge Competency of Certified English Teachers - Ince Rezky Naing (JURNAL PENA EDUKASI, 2025)
Advancements in technology have significantly impacted the integration of technology into educational practices. However, incorporating technology into teaching remains challenging, largely due to the insufficient training received by some educators in this area. Effective technology integration, particularly in English as a Foreign Language (EFL) settings, necessitates the use of the Technological Pedagogical Content Knowledge (TPACK) framework. This study aimed to examine the TPACK competencies of certified high school English teachers. A case study method was employed as it was deemed the most suitable approach for this research. Data were collected through semi-structured interviews with five certified high school English teachers. The findings revealed that the participants considered themselves proficient in nearly all sub-dimensions of TPACK. The study concluded that certified high school English teachers possess a strong understanding of TPACK and the ability to apply it effectively. This study highlights the importance of raising awareness among English teachers regarding the TPACK framework. Ultimately, it contributes to the development of English teachers' competencies through TPACK, thereby enhancing the quality of the teaching and learning process